Handbook of Green Chemistry - Anastas, Paul T. (Wiley, 2012)
The Handbook of Green Chemistry is a landmark publication in green chemistry. Edited by the inventor of the 12 principles of Green Chemistry, Paul Anastas, the Handbook of Green Chemistry is a one-stop resource covering green catalysis, green solvents, green processes and green products over 12 volumes of content.